2010
DOI: 10.1002/path.2791
|View full text |Cite
|
Sign up to set email alerts
|

Signalling networks associated with urokinase‐type plasminogen activator (uPA) and its inhibitor PAI‐1 in breast cancer tissues: new insights from protein microarray analysis

Abstract: The urokinase-type plasminogen activator (uPA) and the main uPA inhibitor PAI-1 play important roles in cell migration and invasion in both physiological and pathological contexts. Both factors are clinically applicable predictive markers in node-negative breast cancer patients that are used to stratify patients for adjuvant chemotherapy. In addition to their classical functions in plasmin regulation, both factors are key components in cancer-related cell signalling. Such signalling cascades are well described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…Protein levels of uPA and PAI-1 were compared with the protein levels of 21 signaling molecules that play a role in breast cancer. The study revealed that protein levels of uPA correlate with expression levels of ERK and Stat3, whereas PAI-1 levels correlated with the levels of uPA receptor and AKT activation, thereby confirming earlier studies performed with cell culture models [61].…”
Section: Reverse Phase Protein Arraysupporting
confidence: 87%
“…Protein levels of uPA and PAI-1 were compared with the protein levels of 21 signaling molecules that play a role in breast cancer. The study revealed that protein levels of uPA correlate with expression levels of ERK and Stat3, whereas PAI-1 levels correlated with the levels of uPA receptor and AKT activation, thereby confirming earlier studies performed with cell culture models [61].…”
Section: Reverse Phase Protein Arraysupporting
confidence: 87%
“…Another advantage of the RPPA is the possibility to quantify the total amount of protein in the sample via the application of purified recombinant proteins one the same slide 15, 16. This method enables to measure protein expression from FFPE tissues more precisely than it is possible by IHC (e.g., for HER2) and implement the analysis of clinical markers, which until now were only measurable from fresh or frozen tissues (e.g.…”
Section: Reverse Phase Protein Microarraysmentioning
confidence: 99%
“…Nevertheless, we successfully established a set of about 50 antibodies for use in RPPA analysis by stringently selecting for specificity and sensitivity by western blot 15, 16 thus providing a starting point for the analysis of major cancer-related signaling pathways from FFPE tissues of cancer patients. Based on this expertise we recently developed an algorithm to validate antibodies for their simultaneous application to extract based and classical morphology based methods (Schuster C, Malinowsky K et al ., in preparation).…”
Section: Reverse Phase Protein Microarraysmentioning
confidence: 99%
See 2 more Smart Citations